Relationship of Knowledge and Attitude with The Implementation of Occupational Safety and Health Management Systems - Haslinah Ahmad; Muhammad Anwar; Ismail Kamba (Hasanuddin Medan, 2022)
Failure in every process or work activity, and when a work accident, no matter how small, will result in a loss effect. Work accidents are a risk faced by every worker who does work with losses not only loss of life and material for workers and employers but also can disrupt the production process as a whole and damage the environment which in turn has a direct impact on the surrounding community. This type of research is analytic which aims to analyse the relationship between knowledge and attitudes with the implementation of the Occupational Health and Safety Management System of P2K3 Management. The population in this study was P2K3 Management totalling 183 people. The number of samples in this study were 46 P2K3 administrators. Sampling by using random sampling. Thus, obtained from each region, namely AFD IV as many as 10 people, AFD V as many as 16 people and AFD VI as many as 20 people. The results of the Chi-Square Test with a 95% confidence level and a value of = 0.05 showed that knowledge and attitudes had a significant relationship with the implementation of the Occupational Health and Safety Management System where the p value of each was 0.007. for knowledge and 0.005 for attitude. It is recommended to carry out regular socialization and training to P2K3 administrators in order to increase their knowledge in implementing occupational safety and health management properly.